1968
DOI: 10.1172/jci105878
|View full text |Cite
|
Sign up to set email alerts
|

Human monoclonal γG-cryoglobulins with anti—γ-globulin activity

Abstract: A B S T R A C T Seven human yG-myeloma proteins which were also cryoglobulins were studied with respect to their reactivity with yG-globulins as well as with regard to their antigenic classification within the yG-heavy chain subclasses. Five of the seven cryoglobulins studied were positive in at least two of the three tests used to assay for anti-y-globulin activity. One protein was only weakly positive in one test system and another was negative in all test systems. The structures which were recognized by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
1

Year Published

1970
1970
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(31 citation statements)
references
References 21 publications
2
28
0
1
Order By: Relevance
“…Similar techniques have been used by Schrohenloher (7) with rheumatoid sera, by Munthe and Natvig (18) with eluates from synovial and other granulation tissues of rheumatoid patients, and by Grey et a1 (45) and Cerottini and Grey (46) with monoclonal IgG cryoglobulins with anti-IgG activity. This method is based on the fact that pepsin digestion of the serum destroys the IgM molecules (47,48) as well as the Fc portion of the IgG molecules, leaving behind F(ab').…”
Section: Discussionmentioning
confidence: 93%
“…Similar techniques have been used by Schrohenloher (7) with rheumatoid sera, by Munthe and Natvig (18) with eluates from synovial and other granulation tissues of rheumatoid patients, and by Grey et a1 (45) and Cerottini and Grey (46) with monoclonal IgG cryoglobulins with anti-IgG activity. This method is based on the fact that pepsin digestion of the serum destroys the IgM molecules (47,48) as well as the Fc portion of the IgG molecules, leaving behind F(ab').…”
Section: Discussionmentioning
confidence: 93%
“…The results of several investigators indicate that this may be the case, even though the basis of this phenomenon has not been explained previously. Grey et al (21) noted that all F(ab')2 fragments of some cryoglobulins with monoclonal IgG-rheumatoid factors bound to normal IgG. The work of Winchester et al (22) suggested that IgGrheumatoid factors may be the primary constituent in synovial fluid complexes from patients with rheumatoid arthritis, since these materials failed to adsorb to solidified normal IgG, even after acid dissociation.…”
Section: Resultsmentioning
confidence: 99%
“…2 Antibodies of the IgG3 subclass in humans and mice have the unique physicochemical property that allows them to self-associate via Fc-Fc interactions and to display cryoglobulin activity, independently of their specificities. [3][4][5][6][7][8] Nucleotide sequence analysis of the variable regions of cryogenic and noncryogenic IgG3 mAbs, in combination with the assessment of mutant antibodies, showed that cryoglobulin activity of IgG3 was associated with the presence of more positively charged amino-acid residues at positions 6 and 23 of the heavy-chain variable domain. 9,10 Moreover, structural analysis of asparagine-linked biantennary complex-type oligosaccharide chains (N-glycans) attached to the CH2 domain of different IgG3 mAbs revealed an inverse correlation between the extent of terminal sialylation and cryogenic activity.…”
mentioning
confidence: 99%